Recycled PET as Reinforcement in UPE Composites: Mechanical Integrity, Thermal Conductivity, and Acoustic Insulation Characteristics - Hashim, Saad Mushtaq; Bdaiwi, Waleed (Annales de chimie (Paris. 1914), 2025)
This study investigates the mechanical, thermal, chemical, and acoustic properties of unsaturated polyester resin (UPE) composites reinforced with recycled polyethylene terephthalate (PET) particles. Micro-sized PET particles (~53 μm), derived from post-consumer plastic waste, were incorporated into UPE at weight fractions of 0%, 2.5%, 5%, 7.5%, and 10% using a hand lay-up technique. The resulting composites were evaluated for compressive and flexural strength, thermal conductivity, FTIR-based chemical structure, and sound insulation performance. Results showed that increasing PET content significantly enhanced compressive strength, achieving a maximum improvement of ~29% at 10 wt% PET. In contrast, flexural strength decreased sharply with PET addition due to filler-induced brittleness and weak interfacial adhesion. Thermal conductivity improved by 29.6% at 5 wt% PET before plateauing, attributed to improved phonon transport at optimal filler dispersion. FTIR analysis confirmed minor thermal degradation at higher PET contents, evidenced by the emergence of hydroxyl bands. Acoustic testing revealed broadband sound attenuation across low, mid, and high frequencies, with up to 23 dB reduction in sound transmission, peaking at 7.5 wt% PET. These findings support the use of recycled PET as a sustainable reinforcing filler for UPE composites in thermal and acoustic insulation applications. A novel approach combining mechanical, thermal and acoustic tests highlights how recycled PET can be used to enhance sustainable composite technologies in many branches of engineering.